Developing Technological Literacy in Papua's Local Policy-Based Learning in Environmental Monitoring: Pengembangan Literasi Teknologi pada Pembelajaran Berbasis Kebijakan Lokal Papua dalam Pemantauan Lingkungan - Khaeriah Dahlan; Rahman; Hardi Hamzah; Nalince Naomi Paraibabo; Ahmad Rezaldi Maulana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service program aims to enhance technological literacy and strengthen STEM (science, technology, engineering, and mathematics) education at SMA Pembangunan V Yapis Waena, Papua, through the introduction of sensor technology based on the Arduino Uno microcontroller integrated with local wisdom. The program addresses key challenges, including limited access to technology, insufficient integration of local contexts into learning, and the lack of students’ hands-on experience in environmental monitoring. The activities were conducted through teacher training, project-based learning, and community collaboration over one semester. The implementation results showed a significant increase in students’ technological literacy and STEM competence, with an average improvement of 30% in conceptual understanding, 60% in programming skills, and 35% in scientific collaboration. Teachers demonstrated greater confidence in utilizing Arduino devices and developing digital learning materials. The program’s outputs include a contextual learning module based on Arduino, simple environmental monitoring prototypes, and a student project exhibition involving the local community. The program has generated measurable impacts, such as improved environmental awareness, stronger collaboration between schools and communities, and the establishment of a locally integrated STEM learning model that can be replicated in other schools across Papua.